Transient hydrodynamic effects influence organic carbon signatures in marine sediments. Issue 1 (December 2018) - Magill, Clayton; Ausín, Blanca; Wenk, Pascal; McIntyre, Cameron; Skinner, Luke; Martínez-García, Alfredo; Hodell, David; Haug, Gerald; Kenney, William; Eglinton, Timothy
Abstract Ocean dynamics served an important role during past dramatic climate changes via impacts on deep-ocean carbon storage. Such changes are recorded in sedimentary proxies of hydrographic change on continental margins, which lie at the ocean–atmosphere–earth interface. However, interpretations of these records are challenging, given complex interplays among processes delivering particulate material to and from ocean margins. Here we report radiocarbon (14 C) signatures measured for organic carbon in differing grain-size sediment fractions and foraminifera in a sediment core retrieved from the southwest Iberian margin, spanning the last 25, 000 yr. Variable differences of 0–5000 yr in radiocarbon age are apparent between organic carbon in differing grain-sizes and foraminifera of the same sediment layer. The magnitude of14 C differences co-varies with key paleoceanographic indices (e.g., proximal bottom-current density gradients), which we interpret as evidence of Atlantic–Mediterranean seawater exchange influencing grain-size specific carbon accumulation and translocation. These findings underscore an important link between regional hydrodynamics and interpretations of down-core sedimentary proxies. Marine sedimentary records and the proxies within play a central role in unlocking our understanding of past climates, yet interpreting the signals they contain can be complex. Here, the authors reveal and discuss the complex effects of hydrodynamics on carbon accumulation in the sediments off the Iberian margin.